Before evening falls: Perspectives of a good old age and healthy ageing among oldest-old Swedish men. (May 2019) - Carstensen, Gunilla; Rosberg, Birgitta; Mc Kee, Kevin J.; Åberg, Anna Cristina
Highlights: Our participants presented themselves as active agents in a dynamic process of finding meaning and sustaining well-being in everyday life. The themes of Adaptation, Sustaining Independence, and Belongingness emerged as central in their understanding of a good old age. The theme Perspectives on Time, a thread linking the other themes, described the importance of a social and emotional continuity to life. Our findings have resonance with models of healthy ageing, but also diverge in important ways. Well-being in later life can be understood by contextualizing present circumstances through the prism of the individual's personal past. Abstract: The late life experiences of men in the oldest-old age group have been under-researched, and their perspectives on ageing successfully neglected. This study explored the perspectives of oldest-old Swedish men on what a 'good old age' and ageing successfully meant to them. A purposive sample of 17 men, aged 85-90 years, was drawn from the Uppsala Longitudinal Study of Adult Men. An interview guide explored participants' perspectives on their ageing experiences and how they viewed ageing successfully. Participants were interviewed twice, with 1–2 weeks between interviews, and both interviews were recorded and transcribed. Content analysis identified four themes: i) Adaptation, concerning the ability to adapt to growing old with increasing limitations; ii) Sustaining Independence, related to financial resources and good health as the foundation for independence; iii) Belongingness, representing close relationships, established friendships, and the significance of the spouse; and iv) Perspectives of Time, also a common thread in all themes, in which past life experiences create an existential link between the past, the present and the future, establishing continuity of the self and enhancing life satisfaction. The participants presented themselves as active agents involved in maintaining meaning and achieving life satisfaction; a process related to the ability to manage changes in life. Our findings have resonance with models of healthy or successful ageing, but also diverge in important ways, since such models do not consider the significance of an individual's life history for their present well-being, and primarily conceptualise health as an outcome, rather than as a resource.